Pelatihan Peningkatan Asupan Protein, Kalsium dan Antioksidan Melalui Pemberian Cookies Berbahan Ceker Ayam dan Daun Kelor - Eka Andriani; Ani Nuraeni; Ratih Kurniasari; Devie Rienzani Supriadi (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
During the Covid-19 pandemic, people began to take better care of their health by consuming nutritious food. Cookies are one of the most popular types of snacks wich we can easily to find it wherever and whenever now. There are many kinds of cookies sells in the market by offering flavors and variants, but no one has offered cookies by adding animal ingredients and fiber that can increase the nutritional content for their product. One of the ingredients that can be added in making cookies is chicken claws and moringa leaves which are made into flour before. The addition of chicken claws flour and moringa leaves is expected to increase the selling value and can utilize local food from underutilized ingredients but have high nutritional content such as protein, calcium and antioxidants. The research products in the form of claw cookies and moringa leaves have been tested in the IPB laboratory and tested organoleptically on semi-trained panelists. In addition,